Reduced Serum PD-L1 and Markers of Inflammation in Response to Alternate Day Fasting With a Low-Carbohydrate Intervention: A Secondary Analysis of a Single-Arm Trial - Rand T Akasheh; Giamila Fantuzzi; Krista A Varady; Ting-Yuan D Cheng; Faiza Kalam (Current Developments in Nutrition)
This secondary analysis aimed to examine the effect of a single-arm alternate day fasting intervention with a 30% low-carbohydrate diet on biomarkers of inflammation and immune activation in adults with obesity. A 12-week weight-loss period was followed by a 12-week weight maintenance period. Anthropometrics and blood samples were collected at baseline and weeks 12 and 24. Multiplex assay was used to measure serum biomarkers including programmed death ligand 1 (PD-L1), interleukin 8 (IL-8), IL-1 receptor antagonist (IL-1ra), chemokine ligand (CCL)2, CCL4, interferon gamma (IFnγ), IFNγ–induced protein 10 (IP-10), and cluster of differentiation 40 ligand (CD40-L). In 28 participants, body weight and fat mass decreased during the weight-loss period but stabilized during the weight maintenance period. Serum PD-L1 decreased from baseline to week 12 (P = 0.005) but not at week 24. Moreover, IL-1ra and CCL4 concentrations decreased from baseline to week 24 (P < 0.001 and P < 0.008, respectively). Changes were not significant for in CCL2, IL-8, CD40-L, IFNγ, or IP-10. In conclusion, alternate day fasting–low carbohydrate modulates circulating immune biomarkers, which may be relevant to diabetes, cancer, and autoimmunity.This trial was registered at clinicaltrials.gov as NCT03528317 (https://www.ncbi.nlm.nih.gov/pmc/articles/PMC6934424/).